Protein tyrosine phosphatase PTPL1 suppresses lung cancer through Src/ERK/YAP1 signaling. Issue 21 (4th October 2022) - Wang, Jing; Li, Shuanghui; Zhang, Xiujuan; Zhu, Ning; Yiminniyaze, Ruzetuoheti; Dong, Liang; Li, Chengwei; Gulinuer, Wumaier; Xia, Jingwen; Li, Jing; Zhou, Daibing; Liu, Xinning; et al.
Abstract: Background: To reveal the function of protein tyrosine phosphatase‐L1 (PTPL1) in lung adenocarcinoma. Methods: Lung cancer cell lines were transfected with short hairpin RNA against PTPL1 (shPTPL1 group) or negative control (shmock group). Quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blotting were used to verify the transfection efficacy. Cell proliferation was analyzed by ethynyldeoxyuridine (EdU), Cell counting kit 8 (CCK8), and colony formation assay after PTPL1 or PTPL1 and yes‐associated protein (YAP1) knockdown. The effect of PTPL1 on tumor growth was examined in a xenograft lung cancer model. Results: PTPL1 was downregulated in various types of lung cancer cell lines. The EdU, CCK8, colony formation assays and investigation using a xenograft lung cancer model indicated that PTPL1 knockdown increased the proliferation of lung cancer cells. Mechanistically, PTPL1 knockdown induced the activation of the Proto‐oncogene tyrosine‐protein kinase SRC (Src)/Extracellular regulated MAP kinase (ERK) pathway and thereby promoted yes‐associated protein (YAP1) nuclear translocation and activation. Conclusions: In our study, PTPL1 played a crucial suppressive role in the pathogenesis of lung cancer potentially through counteracting the Src/ERK/YAP1 pathway. Abstract : Knockdown of PTPL1 increases the proliferation of lung cancer cells and induces the activation of the Src/MEK/ERK signaling pathway, and promoted nuclear translocation of Yes‐associated protein (YAP1).